Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Nano-thiophene-graphdiyne engineered buried interface toward homogeneous crystallization of perovskite films - Yutongyang Fu; Le Liu; Zhibin Yu; Rui Han; Yilin Chang; Yunxin Zhang; Wenfei Guo; Bin Huang; Jiajia Du; Wenfeng Yang; Tonggang Jiu (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

Study on the distribution characteristics and toxic risks of trace elements in the eggs of green turtles (Chelonia mydas) nesting on the Xisha Islands - Xiang Li; Li Jian; Minyu Fu; Henyi Zhang; Yuxin Zhang; Rui Guo; Jichao Wang (Environmental Research, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Identification of a hypoxia-related gene signature associated with childhood asthma - Wenlie Chen; Yuanlu Huang; Li Lei; Rui Zhang; Li Fu; Jinwen Liao; Shaohua Wang; Zhenzhuang Zou (Genes & Genomics, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Row-based kiwifruit counting pipeline for smartphone-captured videos using fruit tracking and detection region adaptation guided by support-post - Jiwei Zhang; Liguo Jiang; Leilei He; Zhenchao Wu; Rui Li; Jinyong Chen; Xiaoxu Sun; Yunfei Xue; Anastasia Grecheneva; Spyros Fountas; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Interfacial electron modulation of FeCo LDH@CoS heterojunction for efficient oxygen evolution reaction - Zhen Guan; Hengzhong Chen; Bin Chen; Lingchen Kong; Zhou Shi; Yu Zhong; Wenjie Li; Wencan Qian; Rui Zhang; Jiang Wu; Zaiguo Fu (Journal of Environmental Chemical Engineering, 2025)

Dose effects of polyethylene microplastics on the degradation of phenanthrene in agricultural soils and its underlying mechanisms - Chengyue Liang; Weilian Fu; Lin Tian; Wumei Xu; Yong Zhang; Tai Xiang; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

The decline in desert drift potential weakens aeolian dust emission - Tong Zhang; Lianyou Liu; Peijun Shi; Gangfeng Zhang; Rui Mao; Xia Xu; Zheng Fu; Honglei Jiang; Cuicui Shi; Li Ma; Zihui Zhao; Jiaojiao Dong; et al. (Global and Planetary Change, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Intelligent Alignment Control for Floating Raft Air Spring Mounting System Under Coupled Hull–Raft Deformation - Jian-Wei Cheng; Wen-Jun Bu; Ze-Chao Hu; Jun-Qiang Fu; Hong-Rui Zhang; Liang Shi (Journal of Marine Science and Engineering, 2025)
Shaft alignment is adversely affected by the increasingly severe coupled hull–raft deformation in deep-diving, highly integrated submersibles, thereby compromising operational safety and potentially amplifying vibration noise. To address to this issue, this paper investigates an intelligent alignment control method for the floating raft air spring mounting system (ASMS) applied to marine propulsion unit (MPU) under coupled hull–raft deformation conditions. A multi-objective alignment control algorithm was developed based on the NSGA-II optimization method within an N-step receding horizon optimal control framework, enabling simultaneous achievement of shaft alignment attitude adjustment, hull deformation compensation, raft deformation suppression, and pneumatic energy consumption. Experimental validation was conducted on two distinct ASMS prototypes to evaluate the control algorithm. Tests performed on the ASMS for MPU (MPU-ASMS) prototype demonstrated effective compensation of hull-induced deformations, maintaining shaft alignment offsets within ±0.3 mm and angularities within ±0.5 mm/m. Concurrently, experiments on the floating raft ASMS for the stern compartment (SC-FR-ASMS) achieved precise control of axial offsets within ±0.3 mm, angularities within ±0.5 mm/m, and vertical displacements of critical monitoring points within ±1 mm. The adaptive control strategy additionally proved effective in suppressing raft deformation while simultaneously optimizing pneumatic energy consumption. This research provides robust theoretical and technical foundations for intelligent vibration isolation systems in deep-sea equipment to accommodate extreme-depth-induced hull deformation and large-scale raft deformation.

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Shelter efficiency of windbreak influenced by stand configuration - Ruijie Zhang; Rui Ma; Yanjun Ma; Fu Zhang; Linyuan Wei; Gazangzhuoma Xie (Biosystems Engineering, 2025)

Cu+ -loaded complex adsorbent in acid modified bentonite for improving carbon monoxide (CO) capture - Jianwei Cheng; Yifan Li; Rui Zhang; Dezhi Ran; Zuyun Chen; Wenhao Hou; Qiang Fu; Zhiguang Tian (Process Safety and Environmental Protection, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Flash elimination of nano-/microplastics from complex matrices with record efficiency and sustainability - Nuan Liu; Yingxin Ji; Feng Tang; Jianxin Fu; Chuntian Qiu; Rui Wang; Zhiyang Zhang; Lingxin Chen; Guoqing Wang (Chemical Engineering Journal, 2025)

Frequent horizontal transfer of AHPND-related plasmid among Vibrionaceae in the rotifers and its implication for shrimp disease management - Songzhe Fu; Ziqiang Zhang; Wenyu Zhao; Rui Wang; Junfeng Hui; Qian Yang (Aquaculture, 2025)

Enhanced immobilization of Cd(II) by successive isomorphic substitution with Ca(II) and Mg(II) from ternary layered double hydroxides - Xiaoxian Zhang; Junnan Rui; Shuyi Yang; Rongbing Fu; Yuping Qiu (Journal of Hazardous Materials, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Reversing anther thermotolerance by manipulating the cis-elements in the promoter of a high-temperature upregulated gene Casein Kinase I in upland cotton - Yanlong Li; Yinuo Fu; Yaoyao Li; Rui Zhang; Jing Yang; Huanhuan Ma; Ling Min; Xianlong Zhang (Science China Life Sciences, 2025)

Modeling and Quantitative Assessment of Critical Defects in Shield Tunnels with Cascading Effects - Xiangyu Chang; Rui Zhang; Jianxiao Mao; Yuguang Fu; Hongyun Fan; Hao Wang (Geotechnical and Geological Engineering, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Identification and characterization of Colletotrichum camelliae, the causal agent of leaf spot of Polygonatum odoratum in China - Rui Zhang; Yiyi Feng; Chun Wu; Ke He; Shaming Fu; Cheng Li (Crop Protection, 2025)

Enhanced effects and mechanisms of Tween80 on aniline biodegradation by newly isolated Pseudomonas veronii T1 - Yufeng Fu; Tingdi Zhang; Chuanyu Qin; Chengwu Zhang; Jintao Ru; Rui Tang; Guoxin Huang; Jian Chen (Journal of Environmental Chemical Engineering, 2025)

Physical modification of cassava starch by alternating magnetic field treatment: Effects on fine structure, retrogradation and in vitro digestibility - Rui He; Jinyu Du; Aiguo Feng; Jie Zhang; Geng Zhong; Naifang Fu; Tao Yang (Food Chemistry, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Variability in maternal transfer efficiency of trace elements in green turtles (Chelonia mydas) - Li Jian; Xiang Li; Xiaobo Zheng; Henyi Zhang; Minyu Fu; Rui Guo; Jichao Wang (Environmental Pollution, 2025)

Ce-doped TiO2 supported RuO2 as efficient catalysts for the oxidation of HCl to Cl2 - Jiahui Liu; Fangyuan Dong; Yaqi Huang; Yanghe Fu; Xinqing Lu; Rui Ma; Fumin Zhang; Shuhua Wang; Weidong Zhu (Journal of Environmental Sciences, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)